ANALYSIS OF THE DAMAGE DEGREE WITH SULPHATE-REPODING BACTERIA COLONIES OF THE NORTH URTABULOK MINE - Rustamov, Mirzokhid (Innovatsion texnologiyalar, 2024)
The presence of sulphate-repoding bacteria (SRB) in an oilfield system can have a negative impact on system performance, causing corrosion, clogging and deposit formation. Therefore, controlling and preventing the growth of SRB is an important task to ensure the efficiency and safety of oilfield systems. The articles, based on laboratory tests, confirmed a high rate of contamination in reservoirs in the Northern Urtabula with colonies of SRBv (more than 106 C/ cm3 ) and the degree of infection in the food supply with colonies in the SRB v (more than 105 C/cm3 ). It has been established that biocontamination in fishing environments in Northern Urtabulak is certainly one of the key factors of corrosion of fishing equipment. Conclusions and recommendations based on the test results are given